1993
DOI: 10.1176/ajp.150.1.19
|View full text |Cite
|
Sign up to set email alerts
|

The phenomenological and conceptual interface between borderline personality disorder and PTSD

Abstract: The authors draw a distinction between the enduring effects that traumas can have on formation (or change) of axis II personality traits (including those found in borderline personality disorder) and acute symptomatic reactions to trauma, called PTSD, that are accompanied by specific psychophysiological correlates. They describe the implications of these conclusions for DSM-IV, therapy, and future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(22 citation statements)
references
References 55 publications
0
19
0
3
Order By: Relevance
“…Trauma appears to have a role in the etiology of both PTSD and BPD although the mechanisms by which trauma influences the genesis (and convergence) of these two disorders is uncertain (Sabo, 1997; Murray, 1993). Gunderson and Sabo propose that early trauma may affect personality development in a way that increases vulnerability for developing PTSD later in life (Gunderson & Sabo, 1993). Characterological traits may comprise an important part of the vulnerability that predisposes only a minority of individuals exposed to trauma to develop PTSD (Kessler et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trauma appears to have a role in the etiology of both PTSD and BPD although the mechanisms by which trauma influences the genesis (and convergence) of these two disorders is uncertain (Sabo, 1997; Murray, 1993). Gunderson and Sabo propose that early trauma may affect personality development in a way that increases vulnerability for developing PTSD later in life (Gunderson & Sabo, 1993). Characterological traits may comprise an important part of the vulnerability that predisposes only a minority of individuals exposed to trauma to develop PTSD (Kessler et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The overlap in phenomenological and conceptual aspects of borderline personality disorder (BPD) and posttraumatic stress disorder (PTSD) has been recognized since their initial inclusion in the third edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-III; Gunderson & Sabo, 1993; American Psychiatric Association, 1980). While placed on different axes of the DSM classification system, both disorders have important relationships with trauma.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, a study comparing different personality disorders found that subjects with BPD tend to suffer more sexual abuse in adulthood [18], probably as a result of a chaotic lifestyle characterized by an unsafe and impulsive sexual activity, among other risk behaviours. On the other hand, some research argues that the higher emotional dysregulation evidenced in BPD subjects could increase the likelihood of anxious reactions in response to a subsequent traumatic event [1,20]. With respect to childhood PTSD as a risk factor for BPD into adulthood, there are no prospective studies aimed at addressing this concern.…”
Section: Theories That Explain the Association Between Ptsd And Bpdmentioning
confidence: 99%
“…In this respect, it is stated that patients with PTSD who additionally show chronic impairments in the development of their personality could be classified as suffering from severe forms of PTSD, in the absence of BPD per se. A construct called ‘complex PTSD' [2], formulated in the 1990s, integrates PTSD with other diagnostic criteria/symptomology, that is: intense emotional dysregulation, negative self-esteem, and interpersonal problems (hostility and/or isolation) deriving from negative schemas about others [1,67,68]. An antecedent to this approach appears in the ICD-10 [61], which refers to the construct ‘enduring personality change after catastrophic experience' (F62.0), a category used to classify those subjects submitted to very traumatic stressors who show prolonged impairments at a cognitive, affective, or interpersonal level.…”
Section: Nosological Status Of Comorbidity Between Ptsd and Bpdmentioning
confidence: 99%
See 1 more Smart Citation